Magnetic hybrid Pd/Fe-oxide nanoparticles meet the demands for ablative thermo-brachytherapy - Rogier van Oossanen; Alexandra Maier; Jérémy Godart; Jean-Philippe Pignol; Antonia G. Denkova; Gerard C. van Rhoon; Kristina Djanashvili (International Journal of Hyperthermia)
Objective To investigate the potential of hybrid Pd/Fe-oxide magnetic nanoparticles designed for thermo-brachytherapy of breast cancer, considering their specific loss power (SLP) and clinical constraints in the applied magnetic field.Methods Hybrid nanoparticles consisting of palladium-core and iron oxide shell of increasing thickness, were suspended in water and their SLPs were measured at varying magnetic fields (12–26 mT peak) and frequencies (50–730 kHz) with a commercial alternating magnetic field generator (magneTherm™ Digital, nanoTherics Ltd.).Results Validation of the heating device used in this study with commercial HyperMag-C nanoparticles showed a small deviation (±4%) over a period of 1 year, confirming the reliability of the method. The integration of dual thermometers, one in the center and one at the bottom of the sample vial, allowed monitoring of homogeneity of the sample suspensions. SLPs measurements on a series of nanoparticles of increasing sizes showed the highest heating for the diameter of 21 nm (SLP = 225 W/g) at the applied frequencies of 346 and 730 kHz. No heating was observed for the nanoparticles with the size <14 nm, confirming the importance of the size-parameter. The heating ability of the best performing Pd/Fe-oxide-21 was calculated to be sufficient to ablate tumors with a radius ±4 and 12 mm using 10 and 1 mg/mL nanoparticle concentration, respectively.Conclusions Nanoparticles consisting of non-magnetic palladium-core and magnetic iron oxide shell are suitable for magnetic hyperthermia/thermal ablation under clinically safe conditions of 346 kHz and 19.1 mT, with minimal eddy current effects in combination with maximum SLP.